Advances in tourism destination marketing managing networks - Kozak, Metin, 1968-; Gnoth, Juergen.; Andreu, Luisa. (Routledge advances in tourism, 2009)
This volume provides original insight into the operational opportunities, challenges and constraints in managing Tourism Destination Marketing.